Field investigation on moisture, heat and deformation behaviors and their coupling effects of expressway in warm permafrost regions. (1st August 2022) - Luo, Xiaoxiao; Ma, Qinguo; Yu, Qihao; Wang, Xinbin; Liu, Youqian; Wu, Guilong
Highlights: The moisture, heat and deformation behaviors of expressway in warm permafrost region are investigated. The coupling effects of moisture, heat and deformation of expressway in warm permafrost region are investigated. A characterization method for deformation difference of expressway is proposed. The stability of expressway in warm permafrost region is discussed. Abstract: Expressways construction in warm permafrost regions is faced with serious permafrost degradation, and expressways stability is closely related to its thermal-hydro-mechanical state. However, the behaviors of moisture, heat and deformation of expressway in warm permafrost regions are not completely clear. In this study, the experimental embankment for the proposed Qinghai-Tibet Expressway built on site is taken as the research object, and the behaviors of moisture, heat and deformation and their coupling effects are studied, and the expressway stability in warm permafrost regions is further discussed. The experimental results show that the permafrost degradation beneath expressway is more serious than that beneath ordinary highway. The moisture distribution is affected by temperature distribution and capillary effect, showing high moisture content in the top and bottom of the embankment and low moisture content in the middle. The expressway presents deformation difference due to the differential degradation of underlying permafrost, and the deformation difference increases with time. The embankment settlement is slow before reaching a new thawing depth, but it develops rapidly after reaching a new thawing depth. Frost heaving occurs in cold season and can counteract the creep of warm permafrost, leaving the embankment in a stable deformation state.